Curriculum Evaluation of Formal Diniyah Education Program at Al-Junaidiyah Biru Islamic Boarding School Using the Cipp Model - Ismail; Nasir Mahmud; Amrah Kasim; ST. Syamsudduha (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STAI Raudhatul Akmal, 2026)
This study evaluates the curriculum implementation program of the Formal Diniyah Education Unit (PDF) at Al-Junaidiyah Biru Islamic Boarding School, Bone Regency, using the CIPP (Context, Input, Process, Product) evaluation model. The research employs a qualitative approach with data collected through interviews, observation, and documentation. Results indicate that: (1) Context evaluation shows the environment and conditions of PDF Ulya Al-Junaidiyah Biru adequately support curriculum implementation, though teacher understanding of the PDF curriculum remains uneven due to lack of training; (2) Input evaluation reveals that while the institution uses four curriculum components (Islamic education, general education, local content, and i’dad), facilities and infrastructure have not met quality standards; (3) Process evaluation demonstrates that teacher preparation remains suboptimal, with conventional teaching models still dominant and limited innovation in learning approaches; (4) Product evaluation shows satisfactory academic achievement, with students ranking 3rd nationally in the 2024 National Examination among 59 PDF Ulya institutions across Indonesia. The study recommends enhancing teacher competencies through systematic training, improving infrastructure quality, developing varied learning methods, and strengthening collaboration between PDF leadership, Dewan Masyayikh, and the Ministry of Religious Affairs to optimize curriculum implementation.